PHYSICAL SERVER AND VIRTUAL SERVER: THE PERFORMANCE TRADE-OFFS - Monjur Ahmed (European Scientific Journal, ESJ, 2013)
﻿﻿Virtualization and virtual computing was one of the core interests of the researchers and the professionals in terms of exploration and deployment of the virtualization technology in IT and computing infrastructure. It was an established fact by then that the blessings of the concept were in the minimization of the tangible infrastructural requirement if virtualization were deployed. But it was always a point of interest and argument whether the performance of the virtual servers would place the virtual computing as a competent substitute compared to its physical server counterpart. Thus the performance tradeoffs between the virtual servers and the physical servers were an issue worth investigating. This paper focuses on this issue where the presentation has addressed on a number of experiments with physical server and virtual server to explore the performance efficiency between them in a comparative way.